SOCRATES IN BABYLON - Damerow, Peter (Revista Brasileira de História da Matemática, 2020)
Socrates never visited Babylon. He probably did not even know that in the Old Babylonian period about 1,000 years before his birth Babylonian scribes produced texts that about 2,000 years after his death would be known, using a seemingly genuine Greek term, as Babylonian mathematics. The focus of this paper then is not the question of where Socrates traveled during his lifetime but rather whether it is feasible to assume that a Babylonian scribe argued about mathematics in the same way that Socrates as a spokesman of Plato did 1,000 years later.